DPP4-deficient congenic rats display blunted stress, improved fear extinction and increased central NPY - Canneva, Fabio; Golub, Yulia; Distler, Jörg; Dobner, Julia; Meyer, Sarah Katharina; von Hörsten, Stephan (Psychoneuroendocrinology, 2015)
Inhibitors of dipeptidyl peptidase 4 (DPP4, CD26) are used for the treatment of type 2 diabetic patients and better glucose tolerance has been confirmed in functionally DPP4-deficient congenic rats (DPP4mut), along with immunological alterations and, interestingly, a stress-resilient phenotype. All these findings are in agreement with the "moonlighting" properties of DPP4, whose proteolytic action is responsible for the inactivation of a number of regulatory peptides including, but not limited to, neuropeptide Y (NPY). Among all candidate substrates, DPP4 displays highest affinity for NPY, an endogenous anxiolytic neurotransmitter that is suggested as a candidate biomarker in post-traumatic stress disorder (PTSD) and depression.Central and peripheral NPY levels were measured by ELISA in DPP4mut and DAwt rats revealing a significantly higher concentration of the peptide in the CSF of DPP4mut animals. This finding positively correlated with the blunted stress phenotype measured on an analgesia-meter. Additionally, when a classical fear-conditioning paradigm was investigated, short-term fear extinction was significantly potentiated in DPP4mut rats as compared to wt controls.Our findings indicate a positive correlation between reduced stress-responsiveness and increased central NPY, in DPP4mut rats. Most interestingly, the behavioral phenotype extends to facilitation of fear extinction. These observations raise further interest in DPP4-modulating drugs for the potential effect on NPY metabolism, as a therapeutic tool for psychiatric conditions such as anxiety disorders and PTSD.
EVALuna2:13098

Efficacy, safety, and pharmacokinetics after switching from infliximab originator to biosimilar SB2 in inflammatory bowel disease patients: A long-term observational, prospective cohort study - Fischer, Sören; Mesfin, Sarah Ellen; Klenske, E.; Schmitt, Heike; Vitali, Francesco; Hirschmann, Simon; Ramming, A.; Zundler, Sebastian; Rath, Timo; Krebs, Sabine; Dörje, Frank; Uter, Wolfgang; et al. (JOURNAL OF CROHNS & COLITIS, 2020)
CRIS-Team WoS Importer:2020-04-10